Exploring the Use of Semantic Mapping in English Language Teaching Classroom - Harahap, Melisa Khoyyiroh; Daulay, Sholihatul Hamidah; Dalimunte, Muhammad (SCOPE: Journal of English Language Teaching, 2025)
The study examined the efficacy of employing semantic mapping as a method for comprehending and enhancing students' vocabulary proficiency. This study was conducted at SMA Swasta Al-Fattah Medan in the tenth grade students. This study investigates the implementation of semantic mapping as a vocabulary instruction strategy in English language teaching classrooms at the senior high school level, specifically focusing on Grade X students. Using a qualitative research design, the study explores both teacher implementation practices and student perceptions of semantic mapping through classroom observations, semi-structured interviews, and document analysis. Data were collected from three English teachers and their respective classes over one semester. The findings reveal that students demonstrate positive perceptions toward semantic mapping, with the majority reporting enhanced comprehension and vocabulary retention. Analysis of student responses indicates that semantic mapping facilitates vocabulary acquisition by creating meaningful connections between words and promoting higher cognitive engagement. The research also identifies successful implementation strategies and challenges faced by teachers, including time management and varying student participation levels. The study concludes that semantic mapping is an effective instructional tool that not only improves vocabulary acquisition but also increases student engagement and motivation in English language learning. These findings contribute to the understanding of effective vocabulary instruction methods in English language teaching and provide practical insights for educators implementing semantic mapping in their classrooms.